Pengaruh Mental Accounting Dan Literasi Perpajakan Terhadap Niat Patuh Pajak Pada Gen Z - Wulandari, Fitri; Lubis, Alvin Syahri; Fajar, Rahmat Ilham; Ramadhania, Syakira; Linawati, Linawati (Prisani Cendekia, 2026)
Tax compliance is a crucial factor in supporting the sustainability of state revenue, particularly among Generation Z, who will become the dominant group of taxpayers in the future. This study aims to analyze the influence of mental accounting and tax literacy on tax compliance intention among Generation Z. The research adopts a quantitative approach with a causal research design. Data were collected through questionnaires distributed to Generation Z respondents and analyzed using multiple linear regression. The results indicate that mental accounting has a positive effect on tax compliance intention, reflecting individuals’ ability to manage and allocate financial resources in a structured manner to fulfill tax obligations. In addition, tax literacy also has a positive and significant effect on tax compliance intention, demonstrating that an understanding of tax regulations, functions, and mechanisms enhances awareness and willingness to comply. These findings suggest that improving tax literacy and strengthening financial management behavior should be prioritized in efforts to enhance tax compliance among Generation Z.